(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This paper proposes the Adaptive Neuro-Fuzzy Interference System (ANFIS) method to realize the track correlation of Radar. ANFIS is used for the first time in inverse model in addition to model of aircraft position radar from the recorded data. The simulation results show that the proposed ANFIS controller has been successfully implemented. Root mean square error is applied to measure the performance of ANFIS that revealed the optimal setting needed for better estimation of the aircraft position. Results with RMSE less than 10-4 also show that the controller with ANFIS yields good tracking performance, valuable and easy to implement.